2021
DOI: 10.1111/jvh.13528
|View full text |Cite
|
Sign up to set email alerts
|

The role of hepatitis B virus core‐related antigen in predicting hepatitis B virus relapse after cessation of entecavir in hepatitis B e antigen‐negative patients

Abstract: This study investigated the ability of hepatitis B core-related antigen (HBcrAg) to predict hepatitis B virus (HBV) relapse in HBeAg-negative patients after cessation of entecavir therapy. A total of 301 HBeAg-negative patients without cirrhosis who had stopped entecavir therapy for at least 12 months were recruited. All patients fulfilled the stopping criteria proposed by the APASL 2012 guidelines. The five-year cumulative rates of virological relapse, clinical relapse and HBsAg loss were 71.6%, 57.3% and 18.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
36
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(36 citation statements)
references
References 29 publications
0
36
0
Order By: Relevance
“…1 ). [12] , [13] , [14] , [17] , [18] , [19] , 27 , [30] , [31] , [32] , [33] , [34] , [35] , [36] , [37] , [38] , [39] , [40] , [41] , [42] , [43] , [44] , [45] , [46] , [47] , [48] , [49] , [50] , [51] , [52] , [53] , [54] , [55] , [56] , [57] , [58] , [59] , [60] , [61] , [62] , [63] , [64] , [65] , [66] , [67] , [68] , [69] , [70] , [71] , [72] One of the studies involved two distinct cohorts, of which one consisted exclusively of individuals with prior severe acute exacerbation and the other consisted of patients who had never experienced such an event. 31 Therefore, 50 studies with 51 cohorts were included in the meta-research analysis.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…1 ). [12] , [13] , [14] , [17] , [18] , [19] , 27 , [30] , [31] , [32] , [33] , [34] , [35] , [36] , [37] , [38] , [39] , [40] , [41] , [42] , [43] , [44] , [45] , [46] , [47] , [48] , [49] , [50] , [51] , [52] , [53] , [54] , [55] , [56] , [57] , [58] , [59] , [60] , [61] , [62] , [63] , [64] , [65] , [66] , [67] , [68] , [69] , [70] , [71] , [72] One of the studies involved two distinct cohorts, of which one consisted exclusively of individuals with prior severe acute exacerbation and the other consisted of patients who had never experienced such an event. 31 Therefore, 50 studies with 51 cohorts were included in the meta-research analysis.…”
Section: Resultsmentioning
confidence: 99%
“…A total of 46 of 50 studies reported data on severe flares or hepatic decompensation, but heterogeneously defined them as hyperbilirubinemia (without or without concurrent coagulopathy), ascites, encephalopathy, and/or variceal bleeding, in addition to abrupt elevation of serum ALT. [12] , [14] , [17] , [18] , [19] , 27 , [30] , [31] , [32] , [34] , [35] , [36] , [37] , [38] , [39] , [40] , [41] , [42] , [43] , [44] , [45] , [46] , [47] , [48] , [49] , [50] , [51] , [52] , [53] , [54] , [55] , [56] , [57] , [58] , [59] , [61] , [62] , [63] , [64] , [65] , [66] , [67] , 69 , 70 , 72 The definition of hyperbilirubinemia was also heterogeneous and could be a level of serum bilirubin ≥2 mg/dl, >3 mg/dl, and >2.5x the upper limit of normal. Similarly, coagulopathy was heterogeneously defined by prolongation of prothrombin time (PT) >3 seconds or an international normalized ratio >1.5 ( Table S7 ).…”
Section: Resultsmentioning
confidence: 99%
“…HBcrAg level is useful for predicting off-treatment sustained response after cessation of NA therapy. Recently, HBcrAg level alone or a combination of HBsAg levels has been proposed [ 247 , 275 ]. SCALE-B score (HBsAg level [S], HBcrAg [C], age [A], ALT [L], and tenofovir [E] used for HBV [B]) including HBsAg and HBcrAg levels at NA discontinuation was suggested for prediction of post-NA relapse and HBsAg loss in Asian CHB patients [ 276 - 278 ].…”
Section: Cessation Of Treatment and Monitoring After Antiviral Treatmentmentioning
confidence: 99%
“…Studies have also reported that HBcrAg can be detected even when serum HBV DNA becomes undetectable or HBsAg is lost ( Seto et al, 2014 ). In a Taiwanese study, the independent risk factor of VR was EOT HBcrAg >4 log U/mL ( Huang et al, 2021 ). Jung et al (2016) showed that EOT HBcrAg >3.7 log U/mL was independently associated with more than three-times higher risk of VR in HBeAg-negative CHB patients.…”
Section: Discussionmentioning
confidence: 99%